Pro LINQ : language integrated query in C# 2008 - Rattz, Joseph C. (Berkeley, Calif. : Apress, 2007)
Describes the features of Pro LINQ along with a collection of LINQ operators, prototypes, and code examples.
Kazalo
Keywords: Microsoft LINQ (računalni softver); Jezici za upite; C#